LANGUAGE LEARNING STRATEGIES EMPLOYED BY SUCCESSFULL STUDENTS IN DEVELOPING ENGLISH-SPEAKING PERFORMANCE - Heriyanti Tahang; Sarmin Sarmin; Yuliana Yuliana; Taslim Taslim (Qalam : Jurnal Ilmu Kependidikan, 2018)
This research aimed to discover the language learning strategies used by successfull students in developing speaking performance in speaking performance at English Language Education Program in Universitas Muhammadiyah Sorong. This research used qualitative method in the form of descriptive qualitative. the participants of this research were taken from the third semester of English Language Education Program in Universitas Muhammadiyah Sorong with the total 6 students. The participants were the students who gained score A in speaking class. Based on the data gathered, the result showed that the students applied both of Direct and Imdirect learning strategies in developing their speaking English Language Education Program in Universitas Muhammadiyah Sorong, namely social strategies, metacognitive strategies, affective strategies in Indirect Strategy and memory strategies, cognitive strategies, and compensation strategies in Direct Strategy. From those of six strategies applied, most of the students tended to apply Indirect Strategy that was social strategies by asking help, working in pair, practicing with the proficient user of English and making small group discussion.